Ocular Trauma during the COVID-19 Pandemic in Sanglah Hospital, Denpasar, Bali From March 2020 to March 2021 - Yuliawati, Putu; Utari, Ni Made Laksmi; Djelantik, AAA Sukartini; Pramita, Ida Ayu Ary; Buddyman, Ivane Jessica (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The coronavirus disease 2019 (COVID-19) is an infectious disease characterized by severe acute respiratory syndrome caused by the coronavirus 2. The implementation of lockdown and social distancing is the efforts made by the government to prevent the spread of this virus. The COVID-19 pandemic has affected the incidence rate of ocular trauma in several means. AIM: This study aimed to evaluate the factors that can cause ocular trauma, from the patient’s characteristics, clinical presentation, etiology, and mechanism of ocular trauma of patients who came to the emergency unit of Sanglah Central General Hospital (RSUP) during the COVID-19 pandemic. METHODS: This study is an observational analytic study with simple random sampling method to evaluate the characteristics of patients with ocular trauma from March 2020 to March 2021. The secondary data were obtained from the medical records including age, gender, address, examination data (visual acuity, duration between trauma and time of seeking medical care, diagnosis, trauma etiology, trauma mechanism, and surgery performed on the patient). RESULTS: In this study the most common was the presence of corpus alienum/foreign body in the cornea, chemical trauma, corneal erosion, canaliculi rupture, and keratitis which are usually caused by photoelectric injury. During the COVID-19 pandemic, new regulations were implemented including patient screening, COVID-19 test before undergoing surgery, patient treatment, and also the use of personal protective equipment for the examiners. Moreover, there were behavioral changes of the people caused by the enforcement of lockdown system and also people’s fear of going to the hospital, especially to a COVID-19 referral hospital such as Sanglah General Hospital; therefore, some patients delayed seeking medical treatment and refused to have surgery at Sanglah General Hospital. CONCLUSION: Our study concluded that the trend of ocular trauma in the COVID-19 era tends to occur in the male population and involves trauma to the cornea, with the most common etiology is caused by the presence of foreign bodies such as gram, wood, or metal. Our finding also showed that despite the implementation of social distancing policies in the COVID-19 pandemic situation, ocular trauma can still be found related to the implementation of the lockdown that has been relaxed during this research.